Research in the sociology of education. - Park, Hyunjoon; Kao, Grace (Research in the sociology of education,, 2018)
"Research in the Sociology of Education" is an important and established series, highlighting how data grid societal contexts shape the educational experiences and outcomes of individual children and youth. Including five single-country studies from settings as diverse as rural China, Germany and the United States, as well as two cross-national comparative studies, this insightful new volume continues the series tradition for publishing research from across a broad range of settings. It demonstrates that various educational issues (including student victimization at school, immigrant-native gaps in educational aspiration, and STEM outcomes) are not limited to specific societies but are relevant worldwide. By exploring national and regional situations and then placing them within this broader context, readers are able to see both the commonality and uniqueness of educational issues around the globe.